Legal Protection for First Trademark Registrants: An Analysis of the Substantive Examination System of Trademarks in Indonesia - Christian Alexsander, Cevin; S. T. Kansil, Christine (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-Undangan dan Ekonomi Islam, 2025)
Ideally, Indonesia’s substantive trademark examination system should provide full protection for the first applicant by ensuring that every application is thoroughly reviewed to prevent overlap, similarity, and potential conflicts with previously registered marks. However, in practice, several issues still arise, including the approval of marks with substantial similarity, inconsistent assessment standards, and the growing number of trademark disputes indicating weaknesses in the implementation of substantive examination. This study aims to analyze the extent to which the substantive examination system ensures legal protection for the first applicant and to identify factors contributing to legal uncertainty. The research employs a normative juridical method by examining statutory regulations, trademark dispute decisions, and academic literature related to trademark protection practices. The findings reveal that although Indonesia adopts the first-to-file principle which should theoretically ensure legal certainty the effectiveness of its implementation remains hindered by examination quality, limited institutional resources, and insufficient harmonization with international standards. This study highlights the need to strengthen the substantive examination system so that legal protection for first applicants can be achieved consistently and fairly.